Multispectral retinal video‐ophthalmoscope with fiber optic illumination. Issue 9 (2nd June 2022) - Kolar, Radim; Vicar, Tomas; Odstrcilik, Jan; Valterova, Eva; Skorkovska, Karolina; Kralik, Martin; Tornow, Ralf‐Peter
Abstract: Multispectral imaging is used in various applications including astronomy, industry and agriculture. In retinal imaging, the single‐shot multispectral image stack is typically acquired and analyzed. This multispectral analysis can provide information on various structural or metabolic properties. This paper describes the multispectral improvement of a video‐ophthalmoscope, which can acquire retinal video sequences of the optic nerve head and peripapillary area using various spectral light illumination. The description of the multispectral video imaging is provided and several applications are described. These applications include multispectral retinal photoplethysmography, visualization of spontaneous vein pulsation and multispectral RGB image generation. Abstract : Multispectral imaging is used in various applications including astronomy, industry and agriculture. In retinal imaging, the single‐shot multispectral image stack is typically acquired and analyzed. This multispectral analysis can provide information on various structural or metabolic properties. This paper describes the multispectral improvement of a video‐ophthalmoscope, which can acquire retinal video sequences of the optic nerve head and peripapillary area using various spectral light illumination. The description of the multispectral video imaging is provided and several applications are described.